Prevalence and associated factors of dental anxiety among adults attending public outpatient dental clinic in the Eastern Province, Sri Lanka - Manori Dhanapriyanka; Prasanna Jayasekara; Abdul Sattar Mohamed Falsy Rumy; Nowzath Athambawa; Ahamed Lebbe Asmath Haseena; Kaleelur Rahuman Mohammadu Salman; Mohamed Buhari Mohamed Mufees (BMC Oral Health)
Abstract Background Dental anxiety has become a major concern for both dental practitioners and patients and prevents a significant proportion of people from attending dental clinics. The present study aimed to determine dental anxiety and associated factors among adult patients attending a public outpatient dental clinic in a base hospital, in the Eastern Province of Sri Lanka. Methods A descriptive cross-sectional study was conducted among 400 adults aged 18 to 75 years awaiting dental treatment. A validated and pretested interviewer-administered questionnaire was utilised, and it included demographic information, past dental treatment, and the Modified Dental Anxiety Scale (MDAS) which was used to assess dental anxiety. Anxiety scores ranged from 5 to 25, with scores of 5–9 classified as less anxious, 10–18 as moderately anxious, and scores above 18 as extremely anxious. Statistical analysis was done using SPSS version 28. Descriptive analysis, correlation test, chi-square test and multiple logistic regression were applied for statistical analysis. The significance level was set at p < 0.05. Results The majority of participants in this sample experienced dental anxiety, with 19% classified as extremely anxious, 70% as moderately anxious, and 11% as less anxious. The mean MDAS score was 14.5 (SD = 4.4). Bivariate analysis revealed that dental anxiety is significantly associated with age group, sex, marital status, employment status, monthly family income, past dental visits, sex of treatment provider and previous dental experiences. Multiple logistic regression analysis indicated that age, sex and postponing dental treatment appointments were significant predictor variables of dental anxiety. Conclusion The findings reveal that the majority of participants in this study experience moderate to high levels of dental anxiety. Notably, younger individuals (under 35 years), females, and those who tend to postpone dental appointments were identified as significant predictors of heightened dental anxiety.